Legal Aspects of Deconversion - Domżalski, Mariusz (Człowiek i Społeczeństwo, 2025)
Guarantees of religious freedom and respect for conscience and beliefs are the foundation of a democratic state governed by the rule of law. Among all human rights, freedom of conscience and religion holds a special place. This freedom has been shaped by numerous and long-lasting social, historical, and philosophical processes. According to Article 53, paragraphs 1 and 2 of the Polish Constitution: “Everyone shall be guaranteed freedom of conscience and religion” and “Freedom of religion includes the freedom to profess or accept a religion of one’s choice, as well as to manifest one’s religion, either individually or collectively, publicly or privately, through worship, prayer, participation in rites, practice, and teaching.” Regulations concerning religious freedom are also included in numerous international legal instruments. The right to change one’s religion includes two components: the right to join a religious community and the right to leave it. The right to change religion is closely linked to the freedom from coercion in matters of faith and worldview. The state is not entitled to decide on the religious beliefs of its citizens, nor to take actions that force them to change their religious convictions. Likewise, discrimination on the grounds of religious affiliation or lack thereof is impermissible. The aim of this article is to examine the concept of deconversion and to analyze the legal regulations in this regard at both national and supranational levels. The study employs the formal-dogmatic method, supplemented by the theoretical-legal method.